Opis zagęszczony, opis rozrzedzony. Kulturoznawczy sposób pojmowania niepełnosprawności - Grzesiak, Hanna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
Thick description, thin description. Cultural way of understanding disability The aim of this article is to present disability from the cultural point of view. Special attention will be paid to Clifford Geertz and his thick description. The phrase thick description is borrowed from Gilbert Ryle. In the classic example one boy’s eye involuntairly twitches while at the same time another boy winks. The physical phenomena are the same but the meaning is different. In understanding disability we have to take into consideration not only the medical, social or biopsychosocial model but cultural context as well.